2010
DOI: 10.1017/s0144686x10000589
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural comparison between academic and lay views of healthy ageing: a literature review

Abstract: The aim of this study is to specify the concept of ‘healthy ageing’ from both western and non-western cultural perspectives, and to compare the views of academics and lay older people. Thirty-four published peer-reviewed full papers in English and Chinese (traditional characters) were identified using electronic database searches. The key components of their definitions of healthy ageing were extracted and categorised into 12 domains. The results show that, in general, lay definitions (as described in 11 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
88
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 55 publications
10
88
1
5
Order By: Relevance
“…Self (1) Partner (2) Children (3) Others ( quality of life [20,26]. Studies conducted both in the east and west have shown that having good and trusting relationship with family and friends which provide care and trustimproves the quality of life whereas having no good and trusting relationships decrease the quality of life [8,27,28].…”
Section: Social Support Variables Mobilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Self (1) Partner (2) Children (3) Others ( quality of life [20,26]. Studies conducted both in the east and west have shown that having good and trusting relationship with family and friends which provide care and trustimproves the quality of life whereas having no good and trusting relationships decrease the quality of life [8,27,28].…”
Section: Social Support Variables Mobilitymentioning
confidence: 99%
“…The concept of filial piety is important to Asians [32] and living with extended families rather than living alone, maintaining close contact with and being supported by their extended families is considered as healthy ageing [5,26,33]. The psychological, social and physical needs of the elderly are met when they live with family members.…”
Section: Social Support Variables Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Definitions of healthy ageing based on subjective assessment of older people have shown that older people's norms, perception and self-awareness of the reality of ageing vary among different cultures (Hung et al, 2010). These differences are mostly based on traditions, religious beliefs and the system of values.…”
Section: Healthy and Successful Ageingmentioning
confidence: 99%
“…Social gerontology following the policy aim presented by WHO, is not only to prolong the duration of later life, but also to improve the quality of life of older people (Hung et al 2010).…”
Section: Introductionmentioning
confidence: 99%